2016
DOI: 10.1007/s00181-016-1067-7
|View full text |Cite
|
Sign up to set email alerts
|

Local labor markets and earnings of refugee immigrants

Abstract: This paper estimates how local conditions at the time of immigration influence later outcomes for refugee immigrants to Norway, exploiting the quasiexperimental nature of the Norwegian system for settlement for "quota" or resettlement refugees. A unique administrative dataset with assigned settlement municipalities is used to identify the causal effect of initial location characteristics. Being placed in a labor market where other non-OECD immigrants do well increases own annual labor earnings up to 6 years af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 9 publications
1
35
0
2
Order By: Relevance
“…Forskningslitteraturen har identifisert effekter av lokale arbeidsforhold ved inntreden på arbeidsmarkedet (Raaum & Røed 2006, for Norge), også for innvandrergrupper spesielt. Mens lav initial arbeidsledighet fremmer sysselsetting blant flyktninger i Sverige opptil ti år etter ankomst (Åslund & Rooth 2007), tyder en ny norsk studie på at slike effekter er svake i Norge (Godøy 2016). Tabell 2 viser at omkring en av tre mannlige flyktninger er sysselsatt i bosettingsåret eller året etter, mens andelen kun er 12,5 prosent blant kvinner.…”
unclassified
“…Forskningslitteraturen har identifisert effekter av lokale arbeidsforhold ved inntreden på arbeidsmarkedet (Raaum & Røed 2006, for Norge), også for innvandrergrupper spesielt. Mens lav initial arbeidsledighet fremmer sysselsetting blant flyktninger i Sverige opptil ti år etter ankomst (Åslund & Rooth 2007), tyder en ny norsk studie på at slike effekter er svake i Norge (Godøy 2016). Tabell 2 viser at omkring en av tre mannlige flyktninger er sysselsatt i bosettingsåret eller året etter, mens andelen kun er 12,5 prosent blant kvinner.…”
unclassified
“…The ethnic enclave perspective argues that living close to (co-ethnic) immigrants may provide access to networks important for jobs, housing, and other nonpecuniary community resources (Clark 1992;Logan et al 2002). Research from Scandinavia has found that immigrants may benefit economically from living close to other immigrants and that proximity to co-ethnics matter for immigrants' settlement patterns (Aradhya et al 2017;Godøy 2017;Åslund et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…They find that poor initial economic conditions can decrease wages for refugees up to 10 years after migration. Godøy (2017) also examined refugees in Norway and found no evidence of a long-lasting wage scarring effect.…”
Section: Introductionmentioning
confidence: 99%